Cardioprotective Potential of Buchanania axillaris on Doxorubicin Induced Cardiotoxicity in albino Rats - Kanagavalli, U (International Journal of Pharmaceutical & Biological Archive, 2014)
Cardioprotective Potential of Buchanania axillaris on Doxorubicin Induced Cardiotoxicity in albino Rats